2017
DOI: 10.1007/s12032-017-1007-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognosis value of the CIMP status combined with MLH1 or p16 INK4a methylation in colorectal cancer

Abstract: Aberrant DNA methylation of CpG islands occurred frequently in CRC and associated with transcriptional silencing of key genes. In this study, the CIMP combined with MLH1 or p16 methylation status was determined in CRC patients and correlated with clinicopathological parameters and overall survival. Our data showed that CIMP+ CRCs were identified in 32.9% of cases and that CACNAG1 is the most frequently methylated promoter. When we combined the CIMP with the MLH1 or the p16 methylation status, we found that CIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In contrast, the likelihood of CIMP in Hispanic patients was indistinguishable from non-Hispanic white patients (OR = 1.04, 95% CI = 0.70-1.55). The association of CIMP-H with gender was studied across 56 studies, representing a total of 22,950 CRC patients [9] , [16] , [17] , [19] , [20] , [21] , [22] , [24] , [25] , [27] , [28] , [30] , [31] , [33] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] . The pooled prevalence of CIMP-H in males and females was 18% (95% CI = 15%-20%) and 26% (95% CI = 22%-29%), respectively, indicating a predisposition for CIMP-H tumors towards female gender (pooled OR = 1.59, 95% CI = 1.40-1.81) .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the likelihood of CIMP in Hispanic patients was indistinguishable from non-Hispanic white patients (OR = 1.04, 95% CI = 0.70-1.55). The association of CIMP-H with gender was studied across 56 studies, representing a total of 22,950 CRC patients [9] , [16] , [17] , [19] , [20] , [21] , [22] , [24] , [25] , [27] , [28] , [30] , [31] , [33] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] . The pooled prevalence of CIMP-H in males and females was 18% (95% CI = 15%-20%) and 26% (95% CI = 22%-29%), respectively, indicating a predisposition for CIMP-H tumors towards female gender (pooled OR = 1.59, 95% CI = 1.40-1.81) .…”
Section: Resultsmentioning
confidence: 99%
“…Our study indicated that there was a positive association between the group with two or more genes with aberrant methylation with advanced cancer stages and prognostic outcome, including TTP and EFS, especially in normal tissue. Recently, growing evidence has demonstrated that DNA methylation profiles are changed by carcinogenic factors at the early precancerous stages in various organs 25,[41][42][43][44] . Different DNA methylation profiles were observed at the chronic hepatitis or liver cirrhosis stage as a precancerous condition for liver cancer 41 www.nature.com/scientificreports www.nature.com/scientificreports/ cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study has reported a similar result using a larger database of CRC cases in the USA, revealing a correlation between a high amount of tissue F. nucleatum DNA and higher CRC-speci c mortality. Evidence has also shown that overexpression of BRAF were markers of the poor prognosis [52,53], Moreover, MSI, the primary causes of which is hypermethylation of the MLH1 promoter, was also associated with the clinical outcomes of CRC [4,6].A relevant study hasshown that microbiota has a relation with MMR, which is the most important mechanism for the appearance of MSI [54]. Furthermore, overexpression of BRAF was also considered the marker of poor prognosis which was consistent with our ndings of prognostic values of F. nucleatum,B.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most common malignancies worldwide, with over half a million deaths per year [1,2].It represents a heterogeneous process with a differ ingset of somatic molecular alteration [3].It has been well demonstrated that the accumulation of both genetic and epigenetic alterations cancontribute to malignant transformation of normal colonic mucosa, leading to the development of CRC. Two molecular pathways have been reported: the microsatellite instability (MSI), and the CpG island methylator phenotype (CIMP) [4][5][6][7].MSI is caused by a defective mismatch repair system,resulting in an alteration in the number of repeated nucleotide(s), which causes frame-shift mutations of the MMR genes (MLH1, MSH2, MSH6, and PMS2) or the germ line deletion of the EPCAM gene [8,9].…”
Section: Introductionmentioning
confidence: 99%